ANALISIS PERAN MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) DALAM MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS SISWA PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN DI SMK - Aldhe Rhiza Chairul (BORJUIS: JURNAL OF ECONOMY, 2024)
This study evaluates the impact of Project-Based Learning (PjBL) model in enhancing the quality of vocational education, particularly in the subjects of Creative Products and Entrepreneurship in vocational high schools (SMK). Through this approach, students are encouraged to actively engage in the learning process and develop their own potential, while the role of teachers is more focused on facilitation. Various studies have shown that the implementation of PjBL successfully improves students' learning outcomes, their engagement in learning, as well as skills and competencies relevant to the workplace. This analysis attempts to measure the extent of PjBL's influence on enhancing critical thinking, creativity, student engagement, collaboration skills, learning motivation, and product design learning outcomes. The results of the study indicate that PjBL has a significant positive impact on improving the quality of vocational education. However, the implementation of PjBL also faces certain challenges, such as intensive material preparation and adjustment of the teacher's role. Therefore, in-depth understanding and adequate support from all relevant parties in the vocational education environment are crucial for effectively implementing this approach.